(untitled) (Research, Society and Development, 2021)
The use of a risk management system is one of the essential aspects for the survival of companies in the construction sector, especially in post-crisis times. However, the process of implementing this system requires changes in the organizational context, generating factors that help or hinder the flow of this process. This research aims to analyze the main facilitating factors and obstacles to approaches directed to business risk management in the national construction sector. To this end, it used a Singapore survey as a reference, adapting its questionnaire and applying it to a non-probabilistic sample, delimited by 102 professionals and specialists working in the national construction sector. The data obtained were analyzed statistically, using the Student’s t test for a single sample, identifying 6 facilitating factors and 16 obstacles, considered critical to the risk management processes in construction companies. Then, the 22 factors were evaluated based on the theories of economics (of E) and organization (of O) and compared to factors of organizational resistance highlighted in the literature. The results showed that the items related to issues of business bureaucracy in the national scenario showed statistically significant differences when compared to the business processes in Singapore.